PENERAPAN ANALISIS KONJOIN RANCANGAN FULL PROFILE DENGAN JENIS RESPON RANKING PADA PREFERENSI MAHASISWA TERHADAP KUALITAS DOSEN SEKOLAH TINGGI ILMU STATISTIK - Fitri Catur Lestari (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2012)
The lecturer is a component in university that has a great role to determine the quality of university. The lecturer quality evaluation is important because of that role. The students who are involved in a learning process should give an evaluation of the lecturer quality by preference. The method that concerns in preference study is conjoint analysis. The conjoint analysis consists of some steps: problem identification, stimuli designs, data collecting, choosing the procedure, and interpretation. The stimuli designs in this research is full profile and the data are collected as ranking respons by interview. The sampling method is purpossive. The samples are selected according to segmentation that are regarded varies among students preference to the quality of lecturer: GPA, level/class, origin of senior high school, gender, and the economic condition(income) of the parents. Based on the relative attribute importance, the students preference of the lecturer quality are: mastery of lecture material, ability to motivate students, character, communication, and learning method. The students preference of lecturer quality differs in segments: GPA, level/class, origin of senior high school, gender, and the economic condition(income) of the parents.